Corneal Diabetes: Where to Next? - Karamichos Dimitrios (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2015)
Diabetes mellitus (DM) or better known as simply diabetes is a group of metabolic diseases in which high blood sugar levels are maintained over a prolonged period. Long term complications include but not limited to heart disease, stroke, kidney failure, and ocular damage. There are two main types of diabetes: Type I (T1DM) and Type II (T2DM). In 2013, an estimated 382 million people were diagnosed with diabetes with type 2 accounting for 90% of the cases. Unfortunately, to date, despite significant amount of research there is no known cure except in very specific cases. DM was one of the first diseases described [1], with the first described cases believed to be T1DM. Originally, the disease was classified as "madhumeha" or "honey urine"[1], and was noted that urine attracts ants. The term diabetes was first used in 230 BCE and was considered as a rare disease. T1DM and T2DM were described and identified in 400-500 by Sushruta and Charaka [1], who associated T1DM with youth and T2DM with being overweight [1]. Today we know that T1DM is characterized by loss of the insulin-producing beta cells of the islets of Langerhans in the pancreas [2,3]. T2DM, on the other hand, is known for insulin resistance and it is the more common of the two [4,5].